Big data analytics for smart transportation - Tan, Judith Yi Ru (2019)
The Singapore urban rail network, interior stations and tracks are highly correlated. If one or some specific stations were disrupted, it would impact the whole network gravely. Therefore, it is pivotal to recognize disruptions happening in these critical stations and put more human and material resources to ensure an efficient and timely “failure response strategy” plan. By using the smart card data provided by Land Transport Authority (LTA) and disruptions events reported in social media, it provides us an opportunity to analyse three key features to find the critical stations that are disrupted.